CHALLENGE ON REGIONAL ECONOMIC IMPACT DURING COVID 19 OUTBREAKS - Radianto, Sambari; Wijayanti, Tri Cicik; Aurelia, Naurah (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
Indonesia officially declared the first case of the corona virus infection that caused Covid-19 in early March 2020. Since then, various counter measures have been taken by the government to reduce the impact of the Covid-19 outbreaks in various sectors. Restrictions on community activities affect business activities which led to economics declination.This study aims to estimate the impact of the COVID-19 outbreaks on the regional economics development.Â This research using composite index to estimate the challenge COVID-19 outbreaksÂ on the regional economic and this was carried out by building an index composite showing the severity of health on one hand and economic performance on the other.This research shows, 34 provinces in Indonesia can be classified into four quadrants: 1) health improving and the economy is improving, 2) health is improving and the economy is deteriorating, 3) health worsening and the economy is improving, and 4) health is deteriorating and the economy is deteriorating. This study aprovide suggestions in order to be more accurate in identifying problems and finding precise solutions, the local government should collect data and research on economic aspects in a fast and precise way, namely 1) the level of the COVID-19 outbreak in the province, 2) risk factors for natural disasters, 3), factors characteristic of economic problems, 4) fiscal burden factors.